Special anticipated pension and the principle of the child's superior interest as a human right in Colombia (2019)
In Colombia, there have been significant advances in guarantees and rights for special protection groups such as children in situations of functional diversity, among the different legal measures, are found; the special anticipated pension, established so that parents with children in situations of functional diversity can withdraw from work and take care of their children. In this sense, from the bibliographic-documentary review with critical analysis, the protection offered by this special pension is analyzed against the principle of the best interests of the child as a human right. Concluding, that its application is in tension with the operational-financial response capacity of the State. © 2019, Universidad del Zulia. All rights reserved.